2018
DOI: 10.1371/journal.pone.0208702
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing beat synchronized running to music

Abstract: The use of music and specifically tempo-matched music has been shown to affect running performance. But can we maximize the synchronization of movements to music and does maximum synchronization influence kinematics and motivation? In this study, we explore the effect of different types of music-to-movement alignment strategies on phase coherence, cadence and motivation. These strategies were compared to a control condition where the music tempo was deliberately not aligned to the running cadence. Results show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
26
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 38 publications
2
26
0
1
Order By: Relevance
“…Similarly, in study 2 TT completion time showed a small decrease in MF+MUSIC vs. MFONLY, and was very similar to BL. This improvement in endurance running capacity and performance when listening to selfselected music is consistent with the literature (Buhmann et al, 2018;Terry et al, 2011). However, a novel finding of our study is that listening to music while mentally fatigued negates the negative impact of MF on endurance running capacity and performance.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, in study 2 TT completion time showed a small decrease in MF+MUSIC vs. MFONLY, and was very similar to BL. This improvement in endurance running capacity and performance when listening to selfselected music is consistent with the literature (Buhmann et al, 2018;Terry et al, 2011). However, a novel finding of our study is that listening to music while mentally fatigued negates the negative impact of MF on endurance running capacity and performance.…”
Section: Discussionsupporting
confidence: 92%
“…Dyer and McKune (2013) found no significant effect of fast (140 bpm) vs slow (120 bpm) tempo music on 20 km cycle completion time but reported significantly greater measures of tension in participants during the fast tempo music trial. Conversely, Buhmann et al (2018) reported a positive relationship between music tempo and preferred running cadence, with subsequent improvements in selfpacing strategies when listening to high tempo music. Since it is hard to determine the optimal music tempo, and other characteristics of music are likely to influence its ergogenic effect (Karageorghis and Priest, 2012a), self-selection of music may be a more effective approach (Buhmann et al, 2018).…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…In locomotion, auditory pacing can be readily provided via a headset. Auditory cues in the form of a beat can be used to influence the movement pattern through a process known as auditory-motor synchronization [11][12][13][14][15][16][17], defined here as the coordination of rhythmic movements, such as steps, to external stimuli, such as metronome beeps. Stable coordination between steps and cues is associated with a strong effect of pacing on the movement pattern [4,18].…”
Section: Introductionmentioning
confidence: 99%
“…Despite these and other limitations, BListener may be useful in applications involving music-based bio-feedback. Previous results in this domain (for example in Moens et al, 2014;Van den Berghe et al, 2020;Lorenzoni et al, 2019;Moumddjan et al, 2019;Buhmann et al, 2018) suggest that beneficial outcomes of human-machine synchronization are conditioned by constancy in co-regulated timing. If timing is of low quality, then beneficial effects will probably be poor or even neglectable, suggesting a dependency of effect on timing constancy.…”
Section: Discussionmentioning
confidence: 94%